Proceedings of the 2017 ACM SIGCHI Conference on Creativity and Cognition 2017
DOI: 10.1145/3059454.3059466
|View full text |Cite
|
Sign up to set email alerts
|

Using Real-time Biofeedback of Heart Rate Variability Measures to Track and Help Improve Levels of Attention and Relaxation

Abstract: The main purpose of the study was to investigate if it was possible for a person to use the real-time biofeedback of their heart rate variability (HRV), recorded from a heart rate monitor watch, to help improve their level of attention and relaxation. Attention and relaxation are important factors affecting creativity, so improvements in 'relaxed concentration' could help enhance creativity. New HRV analysis algorithms were developed and tested together with three different user interfaces to explore how the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…We surveyed the literature for flow state feedback, and found that except games [6] which are designed especially to induce flow, most studies investigated simple activities, such as those performed through mobile or web applications [7]. Furthermore, the activities described in those studies, used internal parameters to give feedback, like speed or the visuals of the task, which is relevant for the experience of flow state [6,8]. However, there are no fixed internal parameters in the case of tennis, since the variables of the activity are unpredictable, such as the interference of the opponent.…”
Section: Introductionmentioning
confidence: 99%
“…We surveyed the literature for flow state feedback, and found that except games [6] which are designed especially to induce flow, most studies investigated simple activities, such as those performed through mobile or web applications [7]. Furthermore, the activities described in those studies, used internal parameters to give feedback, like speed or the visuals of the task, which is relevant for the experience of flow state [6,8]. However, there are no fixed internal parameters in the case of tennis, since the variables of the activity are unpredictable, such as the interference of the opponent.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have used various methods for stress inducements, such as the International Affective Picture System ( Hosseini and Khalilzadeh, 2010 ), sound ( Wijsman et al, 2013 ), stress situation templates ( de Santos Sierra et al, 2011 ), reaction time measurement game ( Zhang, 2017 ), arithmetic problems ( Jun and Smitha, 2016 ), chess game ( Fuentes-García et al, 2019 ; Villafaina et al, 2019 ), cyber game ( Williams et al, 2000 ; Loudon et al, 2017 ), delivering speech ( Šalkevicius et al, 2019 ) and movies ( Kolodyazhniy et al, 2011 ). However, in the present research, a money game was developed to induce stress based on the reaction speed game used by Sobotka et al (1992) .…”
Section: Methodsmentioning
confidence: 99%